Phytochemicals and colorectal cancer: About polyphenols (2024)
ABSTRACT: Dietary consumption of polyphenols, found in fruits and vegetables, has been associated with a potentially protective role in colorectal cancer (CRC). To establish the state of knowledge regarding advances in polyphenols, CCR and action mechanisms a systematic review and an analysis of information available until 2021 were made. Results indicate that only some polyphenols have in vitro, preclinical and clinical studies. These studies showed that polyphenols will inhibit human CRC cell invasion, migration, metastasis formation, tumor growth. Action mechanisms involve signaling pathways that modulate genes, proteins, markers or cell death inductors, like the AMPK pathway, caspases, Bcl-2, p-Akt, and NF-kB, lysosomal and mitochondrial dysfunction, cellular cycle arrest, among the best known and implied in CRC. Overall, in vitro, preclinical and clinical data on phytochemicals against CRC are still not sufficient and therefore the preventive or therapeutic impacts of dietary phytochemicals on CRC development deserve further research.